2d+c+4=0

Simple and best practice solution for 2d+c+4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2d+c+4=0 equation:


Simplifying
2d + c + 4 = 0

Reorder the terms:
4 + c + 2d = 0

Solving
4 + c + 2d = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + c + -4 + 2d = 0 + -4

Reorder the terms:
4 + -4 + c + 2d = 0 + -4

Combine like terms: 4 + -4 = 0
0 + c + 2d = 0 + -4
c + 2d = 0 + -4

Combine like terms: 0 + -4 = -4
c + 2d = -4

Add '-2d' to each side of the equation.
c + 2d + -2d = -4 + -2d

Combine like terms: 2d + -2d = 0
c + 0 = -4 + -2d
c = -4 + -2d

Simplifying
c = -4 + -2d

See similar equations:

| 15x+3=3(5x+1) | | 5(3x+1)=15x | | 5x-6=12(0.75x-0.3)+10 | | 5x-14=16+10x | | x^2-6x+3y+6=0 | | .09x+.12*5=.10(x+5) | | (8w+17)(11w-23)=0 | | u^2+2-30=0 | | 20=2(2w+w-2) | | x^2+26x+27=0 | | 7+4(0.5+3x)=-15 | | 12+8y-7y=25 | | (-8x^2y)(x^9y^8)= | | (-8x^2y)(x^9y^8)=-8x^11y^9 | | 3(x-2)-4=2 | | -10.3=7.5+2v | | -(-1+7x)-6(-7-x)=36 | | 5x-3=4(x+8)-10 | | y^5-5y^2=0 | | 4w=77.2 | | 2(4x+28)=16 | | 3842=12(-8+5f) | | 450=-75p | | (x-2+3i)(x-2-3i)= | | k-8.4=-3.1 | | 24x-4x=12+4x | | 9y-18y=11-(14y+19) | | 9x+.12*5=.10(x+5) | | 4y-3+2y=6y+8-y | | 6x-3+4x=13 | | 4y-3+2y=6y | | lne^5=b |

Equations solver categories